Hemodynamic conundrum of thyroid storm induced acute heart failure: a challenging case in remote area. - Andryan, Dya P; Oetama, Susandy; Lilysari, Oktavia (The Indonesian Heart Association, 2025)
Background Thyroid storm (TS) is an acute and critical presentation of hyperthyroidism. It can lead to multiple organ dysfunction and has high rate of mortality. Heart failure is one of grave complication of hyperthyroidism and thyroid storm. Rapid progression of TS can lead to hypoperfusion and shock even with normotensive blood pressure and normal hemodynamic parameter. Unfortunately, prevalence of hyperthyroidism majority in developing area who lack of advanced medical facility.1 This case presentation aims to present the rare condition of acute high output failure secondary due to thyroid storm with hypoperfusion and normotensive shock. Case Illustration A 28-year-old man came to the emergency department of private hospital in East Borneo with worsening dyspnea on effort since three days before admission. His blood pressure was 169/103 mmHg with irregular heart rate at 135-148 bpm. His axillary temperature was 37.9° C. ECG showed rapid atrial fibrillation with Ashman phenomenon. Chest x-ray revealed cardiomegaly with flattened cardiac waist and lung infiltrate. His echocardiogram has hyperdynamic LV with LVEF 70%, normal RV function, concentric LV hypertrophy, and increased LAVi (51.19 mL/m2). From initial echocardiogram hemodynamic assessment, eRAP was 15 mmHg, CO was 6.5 to 7.4 L/min, SVR was 1167 to 1329 dyne/sec/cm-5. His peak E wave velocity was 92-95 cm/s, His fT4 was increased (100 ng/dL) while TSH was reduced (0.007 mU/L). H2FPEF score estimated 38.7% probability of heart failure with preserved ejection fraction (HFpEF). Burch-Wartofsky score was 60, suggesting thyroid storm. He was diagnosed with acute high output heart failure secondary to thyroid storm due to uncontrolled Grave’s Disease, and AF rapid ventricular respond. During follow up in intensive care unit (ICU), patients underwent hypoperfusion with normotensive blood pressure (normotensive shock). norepinephrine was initiated. Patient keep deteriorating, and then passed away in our critical care unit at day of 7th Conclusion Thyroid storm induced acute heart failure might have conundrum presentation due normotensive and good cardiac output, give false impression of hemodynamic condition. Clinical presentation was very important to identify hypoperfusion and aggressive treatment was needed to stabilize patient condition.